Morgagni-Larrey hernia in an adult patient - V.N. Makhutov; D.V. Lebedeva; D.A. Shevchenko; E.G. Grigoryev (Байкальский медицинский журнал)
The article discusses a treatment of a 30-year-old patient with a newly diagnosed diaphragmatic Morgagni-Larrey hernia. Among diaphragmatic hernias, Morgagni-Larrey pathology occurs in 26 % of cases, mostly on the right side. Data on access options for abdominal-mediastinal hernias are presented. In the presented case report, the planned surgical intervention was performed from laparotomy access. The hernia content was represented by a transverse colon and a large omentum, as in most reported cases. We removed the hernial sac and performed plastic repair of the defect with local diaphragm tissues. Taking into account that the discussed pathology decreases the quality of life and has a risk of complications, it is appropriate to perform elective surgical interventions in such patients. Choice of operative access, technique of diaphragm plastic surgery and need for the hernial sac excision are the matters of further consideration.